한국형 내시경역행담췌관조영술 질 평가 지표 - 김기현; Ki-hyun Kim; 전형구; Hyung Ku Chon; 송태준; Tae Jun Song; 안동원; Dong Won Ahn; 이엄석; Eaum Seok Lee; 이윤나; Yun Nah Lee; et al. (The Korean journal of gastroenterology, 2024)
Endoscopic retrograde cholangiopancreatography (ERCP) is a procedure that requires abundant clinical experience and endoscopic skills, and can lead to various complications, some of which may progress to life-threatening conditions. With expanding indications and technological advancements, ERCP is widely utilized, enhancing procedural accessibility. However, without proper quality management, the procedure can pose significant risks. Quality management in ERCP is essential to ensure safe and successful procedures and meet societal demands for improved healthcare competitiveness. To address these concerns, the Korean Society of Pancreatobiliary Endoscopy has developed a Korean-specific ERCP quality indicator reflecting domestic medical environments and realities. Initially, based on a review of foreign ERCP quality indicators and related literatures, key questions were formulated for five pre-procedural items, three intra-procedural items, and four post-procedural items. Descriptions and recommendations for each item were selected through peer evaluation. The developed Korean-specific ERCP quality indicator was reviewed by external experts based on the latest evidence and consensus in this fields. This Korean-specific indicator is expected to significantly contribute to improving ERCP quality in Korea, as it is tailored to local needs. (Korean J Gastroenterol 2024;84:111-122)